Influence of Added Molybdenum on the Activity of DESONOX Catalysts - Agnieszka Marcewicz-Kuba; Dobiesław Nazimek (Adsorption Science & Technology)
The catalytic removal of SO 2 from combustion gases has been studied on the grain plane of a hard coal, being competitive with classical desulphurization processes. The method proposed for the removal of SO 2 from combustion gases described in this paper is quite different from wet classical desulphurization methods. Studies of the influence of molybdenum concentration on the catalytic activity of a number of DESONOX catalysts are reported. The influence of the total surface area and other physicochemical properties of the catalyst on its behaviour have been studied.